The Size of the Viral Inoculum Contributes to the Outcome of Hepatitis B Virus Infection - Asabe, Shinichi (American Society for Microbiology (ASM), 2009)
The impact of virus dose on the outcome of infection is poorly understood. In this study we show that, for hepatitis B virus (HBV), the size of the inoculum contributes to the kinetics of viral spread and immunological priming, which then determine the outcome of infection. Adult chimpanzees were infected with a serially diluted monoclonal HBV inoculum. Unexpectedly, despite vastly different viral kinetics, both high-dose inocula (10(10) genome equivalents [GE] per animal) and low-dose inocula (10° GE per animal) primed the CD4 T-cell response after logarithmic spread was detectable, allowing infection of 100% of hepatocytes and requiring prolonged immunopathology before clearance occurred. In contrast, intermediate (10(7) and 10(4) GE) inocula primed the T-cell response before detectable logarithmic spread and were abruptly terminated with minimal immunopathology before 0.1% of hepatocytes were infected. Surprisingly, a dosage of 10(1) GE primed the T-cell response after all hepatocytes were infected and caused either prolonged or persistent infection with severe immunopathology. Finally, CD4 T-cell depletion before inoculation of a normally rapidly controlled inoculum precluded T-cell priming and caused persistent infection with minimal immunopathology. These results suggest that the relationship between the kinetics of viral spread and CD4 T-cell priming determines the outcome of HBV infection.